Balancing precarious work and care: interviews with women workers 2015-2017 - Grabham, Emily (UK Data Service, 2018)
This data consists of 32 semi-structured depth interviews conducted between June 2015 and January 2017 to capture women's experiences of balancing precarious paid work alongside unpaid care obligations. Respondents were all women with current or recent experience of precarious work and unpaid care living in the mainland UK. Precarious work is defined in this project either (1) as work that falls outside of the 'standard employment relationship' model (influential in legal and policy debates) due to length or type of contract (e.g. temporary or 'zero hours' contracts), or (2) as precarious for another subjectively identified reason, including institutional factors concerning the structure and allocation of work through organisations (e.g. a long term very short hours permanent contract in a supermarket exposing the worker to low pay and restricted career development). Care obligations include care for dependent children, adults, and those with disabilities. Most interviews were conducted in person. Some interviews were conducted as 'walking interviews' to aid understanding of women's daily lives; others were conducted by skype or telephone. Interview data is being used alongside legal research to understand: (1) the extent to which women's experiences of precarious work feature in current law and policy concerning 'family-friendly' rights, and (2) how women's experiences augment or challenge current legal and policy debates in this area. This socio-legal project will use new qualitative research on women's working lives to propose a radical re-evaluation of UK labour law and policy. Most UK labour law is based on the 'standard employment relationship' (SER), which is a relic of the post World War Two industrial era. The SER assumes that most workers are in permanent, full time work with a single employer, and that workers do not have any obligations to care for children or dependents. A key problem for UK policy-makers is that the SER is modelled on, and contributes to, embedded inequalities between women and men in the workplace, and that it continues to place the burden of unpaid care on women. This project will undertake the first in-depth research into the experiences of those people who are most likely to be disadvantaged by the gender assumptions in the SER: precarious female workers with care commitments. It will investigate how the legal frameworks stemming from the SER affect the day to day lives of women balancing precarious work and care.This empirical data will then be used to feed into a new gender-sensitive vision for UK labour law and policy.